Two Decades of HEPA Europe: Advancing Physical Activity Promotion Across the European Region (Baltic Journal of Sport and Health Sciences, 2026)
Background: The Health-Enhancing Physical Activity (HEPA) Europe network was established in 2005 to promote physical activity (PA) related research, policy, and practice across the World Health Organization (WHO) European Region. It was founded on early recognition of the essential role of regular PA for health, contributing to the prevention of non-communicable diseases and the promotion of mental, physical, and social wellbeing but before related European policy frameworks emerged.Nature of the Network: Formally launched under the auspices of the WHO Regional Office for Europe (WHO/Europe), HEPA Europe has grown into a multidisciplinary and cross-sectoral network of over 250 member institutions from 41 WHO European member states. These include governmental bodies, academic institutions, and non-governmental organisations working in fields such as PA, sport, health, education, urban planning, and transport. The network supports collaboration through working groups, an annual conference, and meetings that facilitate the exchange of knowledge, best practices, consortia building for European Union (EU) funded projects, and policy development. It provides tools and evidence for policy and practice to address the insufficient levels of PA and increasing sedentary behaviour across the WHO European Region.Recent Developments: In the recent years, HEPA Europe has strengthened its position by creating an early career development section to support young scientists and professionals at the beginning of their careers in the field of PA promotion. In addition, HEPA Europe worked actively to collaborate with the EU PA Focal Points network, created in 2014, to support implementation of the HEPA Monitoring Framework, established to monitor the implementation of the EU PA Guidelines. HEPA Europe must broaden engagement across sectors and regions, improve sustainability, and strengthen the research–policy–practice link to maintain its impact.Keywords: Network, exercise, public health, governance